2016
DOI: 10.1111/exd.12897
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Notch signalling contributes to hypertrophic scar formation by modulating the phenotype of keratinocytes

Abstract: Hypertrophic scar (HS) is characterized by fibroblast hyperproliferation and excessive matrix deposition. Aberrant keratinocyte differentiation and their abnormal cytokine secretion are said to contribute to HS by activating fibroblasts. However, the signalling pathway causing the aberrant keratinocytes in HS has remained unidentified thus far. Given that Notch signalling is crucial in initiating keratinocyte differentiation, we hypothesized that Notch signalling contributes to HS by modulating the phenotype o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Jagged1 upregulation in pulmonary capillary endothelial cells induces Notch signaling in lung fibroblasts, which results in fibrosis [ 11 ].Zhu et al showed that Notch signaling is elevated during PDF-induced peritoneal fibrosis [ 12 ]. In addition, the Notch pathway was hyperactivated in skin biopsy samples from patients with scleroderma [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jagged1 upregulation in pulmonary capillary endothelial cells induces Notch signaling in lung fibroblasts, which results in fibrosis [ 11 ].Zhu et al showed that Notch signaling is elevated during PDF-induced peritoneal fibrosis [ 12 ]. In addition, the Notch pathway was hyperactivated in skin biopsy samples from patients with scleroderma [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since Notch and TGF-β signaling converges in HS formation regulation ( 8 , 27 ), we further evaluated the expression of key molecules in these signaling pathways in macrophages isolated from PVA exudates. The macrophages from emodin-treated rats had significantly decreased protein levels of Notch1, Notch4, and Hes1 compared with those from the Control group ( Figure 5A ; Notch1, P<0.01, Figure 5B ; Notch4, P<0.01, Figure 5C ; Hes1, P<0.05, Figure 5D ).…”
Section: Resultsmentioning
confidence: 99%
“…Collectively, these results suggested that TGF-b downregulation was involved in emodin-suppressed HS formation and fibrosis in rats. Emodin inhibited the Notch and TGF-b signaling pathways in macrophages from PVA sponge-induced wound in rats Since Notch and TGF-b signaling converges in HS formation regulation (8,27), we further evaluated the expression of key molecules in these signaling pathways in macrophages isolated from PVA exudates. The macrophages from emodin-treated rats had significantly decreased protein levels of Notch1, Notch4, and Hes1 compared with those from the Control group (Figure 5A; Notch1, Po0.01, Figure 5B; Notch4, Po0.01, Figure 5C; Hes1, Po0.05, Figure 5D).…”
Section: Emodin Downregulated Tgf-b Expression In Pva Exudatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal keratinocyte differentiation and their abnormal cytokine secretion are two factors demonstrated to contribute to tissue fibrosis and contraction by activating fibroblasts 74-76. The epidermis maintained its original appearance in the PHCS group, and epidermal ulcers were soon covered with new, thin epidermis within 3 days in the HCS group; while the STSG group showed less recovery (Figure 5).…”
Section: Discussionmentioning
confidence: 99%